Economic Security from the perspective of the Copenhagen School: Case Study of Economic Security in the Kurdistan Region – Iraq - Salih Omar Issa; Parwez Rahim Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In this study, we have tried to highlight the economic security threats of the Kurdistan Region within the framework of the Copenhagen School theory, accordingly, because the Copenhagen school can reveal the hidden threats and dangers within the framework of security issues by presenting five areas and the security sector (political, military, societal, economic and environmental). This research discusses the theory of economic security in the Kurdistan Region, apart from the theory of economic security. Finally, we have come to some conclusions, the most important of which were that all the security sectors have an impact on the security issues in general and the issue of economic security in the Kurdistan Region, and then in recent years, the economic insecurity, the consequences and related issues, particularly the decline in oil prices, budget cuts and salaries by Iraq due to political conflicts. The economy is a single source of oil and Baghdad’s budget, which has faced economic insecurity and has increased the unemployment, poverty and youth migration in the Kurdistan Region, according to which it has put the Kurdistan region's societal insecurity.